Zaračunavanje davka na dodano vrednost pri nabavi in zagotavljanju dostopa do elektronskih informacijskih virov v Sloveniji in v Evropski uniji - Mandelj, Tilen (Knjižnica, 2010)
Tax legislation system in the Republic of Slovenia as well as that of the European Union does not keep pace with the rapid technological development. A lot of problems arise in the field of purchasing and providing access to electronic information sources, namely electronic journals which are very important to disseminate research results. Problems arising from the application of the EC Directive 2006/112in the Slovenian legislation system are described. The goal that the Value Added Tax (VAT) would not affect the international competitiveness of the EU Member states was not met. Different levels of general and reduced tax rates and even different levels of taxation of electronic information sources put Member States in unequal positions. Tax regimes in Member States and their responses to the problem of VAT are discussed. The article shows the complexity of electronic information sources which can partly be taxed as services and party as goods in electronic form. A simulation of expenditure on electronic information sources at different tax rates and possible changes of tax legislation are presented.
Keywords: bibliotekarstvo; library science; knjižnično gradivo; nabava; purchasing; nakup; davek na dodano vrednost; elektronski informacijski viri; Slovenia; Slovenija; European Union; Evropska unija